Efficacy and safety analysis of non-radical surgery for early-stage cervical cancer (IA2 ~ IB1): a systematic review and meta-analysis - Zeng, Siyuan; Xiao, Simin; Xu, Yang; Yang, Ping; Hu, Chenming; Jin, Xianyu; Liu, Lifeng (Frontiers in Medicine, 2024)
Objective: Radical hysterectomy has long been considered as the standard surgical treatment for early-stage cervical cancer (IA2 to IB1 stages), according to the 2009 International Federation of Obstetrics and Gynecology. This study aims to conduct an in-depth evaluation of the effectiveness and safety of non-radical surgery as an alternative treatment for patients with early-stage cervical cancer.Methods: A systematic search of online databases including PubMed, Embase, and the Cochrane Library was conducted to identify relevant literature on surgical treatment options for early-stage cervical cancer. Keywords such as "cervical cancer," "conservative surgery," "early-stage," "less radical surgery," and "simple hysterectomy" were used. Meta-analysis was performed using Stata 15.0 software, which included randomized controlled trials (RCTs) and cohort studies.Results: This meta-analysis included 8 eligible articles covering 9 studies, with 3,950 patients in the simple hysterectomy (SH) surgery group and 6,271 patients in the radical hysterectomy (RH) surgery group. The results indicate that there was no significant difference between the two groups in terms of the Overall Survival (OS)